The Declaration of Helsinki on Medical Research involving Human Subjects: A Review of Seventh Revision - Shrestha, Badri; Dunn, Louese (Journal of Nepal Health Research Council, 2020)
The pinnacle of success achieved by the medical science and the benefits accrued to the patients have become possible through the medical research where human participants in the research are exposed to hazards inherent to the experiments. To protect the human subjects and to maintain high ethical standards, the World Medical Association has adopted “The Declaration of Helsinki” in 1964. After two years of consultation with the experts throughout the world, the seventh revision of the Declaration was adopted on 19th October 2013 in Brazil. The aim of this article is to review the seventh revision of the Declaration of Helsinki in relation to medical research involving human subjects and highlight the amendments made in the latest revision which are relevant to clinical research in human subjects. The latest revision has made four substantial changes on the existing Declaration, whch include dealing with the compensation of the trial-related injuries, approval of use of placebos in the clinical trials, protection of vulnerable groups and the post-trial provisions. The implications of these amendments in the clinical research are highlighted. Keywords: Consent; Declaration of Helsinki; ethics; experimental medicine; research; seventh revision.